2019
DOI: 10.1016/j.electacta.2019.134635
|View full text |Cite
|
Sign up to set email alerts
|

Tris(β-ketoiminato)ruthenium(III) complexes: Electrochemical and computational chemistry study

Abstract: Research highlights • Ru III/IV , Ru III/II redox couples, as well as ligand based reduction of Rh II complex • Separate Ru III/IV redox couples for fac and mer isomers • DFT calculations provide understanding of the locus of the observed redox couples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For complexes containing large R substituents, it is expected that the mer isomers are more stable, since they are less affected by steric hindrance caused between bigger R substituents, when compared to their fac isomers. 25 The mer isomers are also expected to be more stable, due to their lower dipole 26,27 (the solvent used for NMR analysis is CDCl 3 ). Experimentally, from the literature, both fac and mer tris (β-diketonato)cobalt(III) isomers were characterized, for example, 20% fac [Co(ba) 3 ] ( 2 ) (based on yield), 28 18% fac [Co(tfaa) 3 ] ( 4 ) (based on NMR measurements), 27,29,30 and both fac and mer [Co(β-diketonato) 3 ] crystal structures are known.…”
Section: Resultsmentioning
confidence: 99%
“…For complexes containing large R substituents, it is expected that the mer isomers are more stable, since they are less affected by steric hindrance caused between bigger R substituents, when compared to their fac isomers. 25 The mer isomers are also expected to be more stable, due to their lower dipole 26,27 (the solvent used for NMR analysis is CDCl 3 ). Experimentally, from the literature, both fac and mer tris (β-diketonato)cobalt(III) isomers were characterized, for example, 20% fac [Co(ba) 3 ] ( 2 ) (based on yield), 28 18% fac [Co(tfaa) 3 ] ( 4 ) (based on NMR measurements), 27,29,30 and both fac and mer [Co(β-diketonato) 3 ] crystal structures are known.…”
Section: Resultsmentioning
confidence: 99%
“…A few other works reported that the aliphatic NH 2 might also react with HCHO; however, there are no clear characterizations to support the reactions. [ 24 ] To confirm the possible reaction of aliphatic NH 2 group with HCHO in water, we carried out a control experiment, in which D‐cysteine with an aliphatic NH 2 was mixed with HCHO, whereas no reaction was observed in 10 h, as confirmed by 1 H NMR [ 25 ] (Figure S3b, Supporting Information). We speculate that, under ambient conditions, aliphatic NH 2 might only adsorb HCHO via physical interactions or hydrogen bonding, while the ONH 2 groups could chemically react with HCHO at the same condition (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The relative energies of the fac and mer isomers of complexes 1-3 showed that the mer isomer will be found in experiment to be the main isomer (> 99.8 % according to the Boltzmann equation). The mer isomers were less affected by steric hindrance caused by the Ph group [29].…”
Section: Dft Optimized Geometry and Properties Of Moleculesmentioning
confidence: 96%